2021
DOI: 10.2169/internalmedicine.5381-20
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Use of Golimumab in Daily Practice for Patients with Rheumatoid Arthritis

Abstract: Objective To evaluate the effectiveness and drug retention rate of golimumab (GLM) for long-term use in daily practice for patients with rheumatoid arthritis (RA). Methods Patients with RA who started GLM therapy with a minimum follow-up period of 52 weeks were included. The patients were divided into a biologic-naïve group and switch group. The disease activity score (DAS) 28-erythrocyte sedimentation rate (ESR) (DAS28-ESR), grip power, and Japanese version of the health assessment questionnaire (J-HAQ) score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In another study conducted with children with Type 1 diabetes, the use of another TNF-α-blocking drug etanercept showed similar favorable effects on the pancreas. 22 Thus, these findings may support why GLM may be a favorable therapeutic in case of AP and AP-related pancreatic complications.…”
Section: Discussionmentioning
confidence: 68%
“…In another study conducted with children with Type 1 diabetes, the use of another TNF-α-blocking drug etanercept showed similar favorable effects on the pancreas. 22 Thus, these findings may support why GLM may be a favorable therapeutic in case of AP and AP-related pancreatic complications.…”
Section: Discussionmentioning
confidence: 68%
“…In the GO-MONO study, GLM monotherapy resulted in good clinical and radiographic improvements ( 14 ). We previously reported the long-term use of GLM at Niigata Rheumatic Center ( 15 ); specifically, we described improvements in grip power associated with GLM treatment. In another study of real-world clinical data, Okazaki et al reported that the safety and effectiveness of GLM treatment were nearly identical between elderly and younger patients ( 16 ).…”
Section: Introductionmentioning
confidence: 99%